Linear growth in young people with restrictive eating disorders: “Inching” toward consensus - Downey, Amanda E.; Richards, Alexis; Tanner, Anna B. (Frontiers in Psychiatry, 2023)
Background While the assessment of acute medical stability in patients with eating disorders should never be minimized, careful attention toward other specific age-related consequences of malnutrition can improve psychological outcomes and reduce long-term, potentially irreversible medical complications, like linear growth impairment. Review While the impact of malnutrition on linear growth is widely recognized, emerging data highlight consensus in several key areas: the time from onset to time of diagnosis, age at illness onset, pubertal stage at illness onset, and adequacy of weight restoration to achieve catch-up growth. This review provides concrete and actionable steps to help providers identify and explore deviations in expected growth and development while prioritizing early and aggressive weight restoration to provide the best opportunity for catch-up linear growth in patients with eating disorders. Conclusion The impact of restrictive eating disorders on growth and development cannot be overstated, particularly in pre- and peripubertal patients. While many consequences of malnutrition are reversible, the loss of genetic height potential may prove irreversible without early and aggressive weight restoration.